Strongly coupled single quantum dot in a photonic crystal waveguide cavity - Brossard, F; Xu, X; Williams, D; Hadjipanayi, M; Hugues, M; Hopkinson, M; Wang, X; Taylor, R (2010)
Cavities embedded in photonic crystal waveguides offer a promising route towards large scale integration of coupled resonators for quantum electrodynamics applications. Here a strongly coupled system consisting of a single quantum dot and a cavity formed by the local width modulation of a photonic crystal waveguide is demonstrated. The resonance originating from the cavity is clearly identified from microphotoluminescence mapping of the scattered signal along the waveguide. The exciton-photon strong coupling regime is obtained by temperature control. © 2011 American Institute of Physics.